RC Boat Trash Collector berbasis Solar Cell sebagai Solusi Pembersihan Sampah Anorganik pada Permukaan Air Sungai - Aditya, Moch. Roghib Kasful Nghoman; Muzdalifah, Putri; Aulia Rahman, Dandi; Tri Saputra, Hilmy; Adi Pratama, Yudha; Entikaria Rachmanita, Risse (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
Currently, wasted is a huge problem in Indonesia. This happens because every day the amount of waste increases along with increasing production without proper processing methods. The average daily waste generation by the community is 52,252.51 tons, and from this data 24.85% is inorganic trash. Most inorganic trash cannot be decomposed by microorganisms or takes a long time to be decomposed by nature. It is estimated that there are 0.48-1.29 million tons of plastic trash per year is found in oceans and lakes. If this continues, more and more losses will be caused, such as river pollution which will cause water erosion and flooding, damage ecosystems in rivers, and can accelerate the spread of pests and diseases. Based on this problem, the application of solar cell-based RC Boat Trash Collector technology aims to assist in cleaning up trash on the surface of river water by using a conveyor mechanism to transport trash. The stages of applying technology to partners consist of problem identification, data collection, pre-production, production and post-production. The implementation of this technology involves cleaning rivers in residential areas and being able to transport 647.8 grams of plastic trash.